DESIGN AND SYNTHESIS OF CHAINED-RESPONSE MULTIBAND FILTERS - BONG CHUNG, DAVID HUA (2020)
Given how important multiband filters are in the current era, little work seems to have come up with methods that can produce multiband filters of more than two passbands with flexibility in inner-band frequency selection, as well as specific bandwidths for each passband. In this research, a novel method known as chainedresponse for multiband filter is proposed. This method can produce multiband filters with the flexibility to set the bandwidths for each passband as well as its inner-band frequency selection. The theory of chained-response is developed where the filtering function together with the coupling matrix is derived. Matrix rotation is then applied to produce the suitable topology. In order to validate the feasibility of the approach, a dual-band filter is designed, simulated and fabricated.